Fortification of Human Milk for Preterm Infants: Update and Recommendations of the European Milk Bank Association (EMBA) Working Group on Human Milk Fortification - Arslanoglu, Sertac; Boquien, Clair-Yves; King, Caroline; Lamireau, Delphine; Tonetto, Paola; Barnett, Debbie; Bertino, Enrico; Gaya, Antoni; Gebauer, Corinna; Grovslien, Anne; Moro, Guido E.; Weaver, Gillian; et al. (Frontiers in pediatrics, 2019)
Evidence indicates that human milk (HM) is the best form of nutrition uniquely suited not only to term but also to preterm infants conferring health benefits in both the short and long-term. However, HM does not provide sufficient nutrition for the very low birth weight (VLBW) infant when fed at the usual feeding volumes leading to slow growth with the risk of neurocognitive impairment and other poor health outcomes such as retinopathy and bronchopulmonary dysplasia. HM should be supplemented (fortified) with the nutrients in short supply, particularly with protein, calcium, and phosphate to meet the high requirements of this group of babies. In this paper the European Milk Bank Association (EMBA) Working Group on HM Fortification discusses the existing evidence in this field, gives an overview of different fortification approaches and definitions, outlines the gaps in knowledge and gives recommendations for practice and suggestions for future research. EMBA recognizes that "Standard Fortification," which is currently the most utilized regimen in neonatal intensive care units, still falls short in supplying sufficient protein for some VLBW infants. EMBA encourages the use of "Individualized Fortification" to optimize nutrient intake. "Adjustable Fortification" and "Targeted Fortification" are 2 methods of individualized fortification. The quality and source of human milk fortifiers constitute another important topic. There is work looking at human milk derived fortifiers, but it is still too early to draw precise conclusions about their use. The pros and cons are discussed in this Commentary in addition to the evidence around use of fortifiers post discharge.